Fluorescence recovery after photobleaching reveals regulation and distribution of connexin36 gap junction coupling within mouse islets of Langerhans - Farnsworth, Nikki L (J Physiol, 2014)
The pancreatic islets are central to the maintenance of glucose homeostasis through insulin secretion. Glucose-stimulated insulin secretion is tightly linked to electrical activity in β cells within the islet. Gap junctions, composed of connexin36 (Cx36), form intercellular channels between β cells, synchronizing electrical activity and insulin secretion. Loss of gap junction coupling leads to altered insulin secretion dynamics and disrupted glucose homeostasis. Gap junction coupling is known to be disrupted in mouse models of pre-diabetes. Although approaches to measure gap junction coupling have been devised, they either lack cell specificity, suitable quantification of coupling or spatial resolution, or are invasive. The purpose of this study was to develop fluorescence recovery after photobleaching (FRAP) as a technique to accurately and robustly measure gap junction coupling in the islet. The cationic dye Rhodamine 123 was used with FRAP to quantify dye diffusion between islet β cells as a measure of Cx36 gap junction coupling. Measurements in islets with reduced Cx36 verified the accuracy of this technique in distinguishing between distinct levels of gap junction coupling. Analysis of individual cells revealed that the distribution of coupling across the islet is highly heterogeneous. Analysis of several modulators of gap junction coupling revealed glucose- and cAMP-dependent modulation of gap junction coupling in islets. Finally, FRAP was used to determine cell population specific coupling, where no functional gap junction coupling was observed between α cells and β cells in the islet. The results of this study show FRAP to be a robust technique which provides the cellular resolution to quantify the distribution and regulation of Cx36 gap junction coupling in specific cell populations within the islet. Future studies utilizing this technique may elucidate the role of gap junction coupling in the progression of diabetes and identify mechanisms of gap junction regulation for potential therapies.